STUDENTS' PERCEPTIONS OF DIFFICULTIES IN HISTORY SUBJECT AT SMA NEGERI MODEL TERPADU MADANI PALU - Inul (Journal of Education and Teaching Learning, 2026)
This study aims to describe students' perceptions of history learning, analyze the influence of students' perceptions on history learning, and describe the level of students' learning motivation in history subjects at SMA Negeri Model Terpadu Madani Palu. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of the school principal, history subject teachers, and eleventh-grade students of SMA Negeri Model Terpadu Madani Palu. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis involved the stages of data reduction, data display, and conclusion drawing. The results of the study indicated that students' perceptions of history learning were generally positive. Students viewed history as an important subject for broadening national insights, shaping character, and understanding the nation's journey. However, some students still experienced difficulties in understanding the chronology of events, remembering the names of historical figures, and memorizing important years in history. Students' perceptions of history learning were influenced by the teacher's teaching methods, the use of learning media, and the relevance of the material to daily life. Furthermore, the level of students' learning motivation was categorized as fairly good and increased when the teacher implemented interactive learning through discussions, the use of audiovisual media, and the provision of contextual examples. Thus, the application of varied and innovative learning methods is able to enhance positive perceptions as well as students' learning motivation in history learning.